Staphylococcus aureus methicillin-resistance mechanisms - Petrović-Jeremić Ljiljana; Kuljić-Kapulica Nada; Mirović Veljko; Kocić Branislava (Vojnosanitetski Pregled)
Background/Aim. In many hospitals in the world and in our country, the spread of methicillin-resistant Staphylococcus aureus (MRSA) is so wide that nowdays vancomycin is recommended for empiric treatment of staphylococcal life threatening infections (sepsis, pneumonia) instead of beta-lactam antibiotics. The aim of this study was to determine the production of beta-lactamases in hospital and community isolates of staphyloococus aureus, i. e. hospital associated MRSA (HA-MRSA) and community associated MRSA (CA-MRSA), the presence of homogeneous and heterogeneous type of methicillin resistance, and border-line resistance in Staphylococcus aureus (BORSA). The aim of this study was also to determine if there was a statistically significant difference between mechanisms of resistance in HA-MRSA and CA-MRSA. Methods. A total 216 clinical Staphylococcus aureus isolates from the General Hospital in the town of Cuprija and 186 ambulance Staphylococcus aureus isolates from the community were examined for the presence of methicillin-resistance using disk-diffusion test with penicillin disk (10 ij), oxacillin disk (1 μg) and cefoxitin disk (30 μg). Betalactamases production was detected by nitrocefin disk and betalactamase tablets. Determination of oxacillin minimum inhibitory concentracion (MIC) was done by agar-dilution method. Results. The prevalence of HA-MRSA was 57.4%, and CA-MRSA was 17.7% (p < 0.05). There was a higher rate of heterogeneous type of resistance among clinical MRSA isolates (11.1%) compared with ambulance ones (3.8%) (p < 0.05). The rates of beta-lactamases production were similar among hospital associated isolates (97.5%), as well as in the community associated isolates (95.5%) (p > 0.05). There were 4.6 % of BORSA hospital isolates and 3.3 % of BORSA ambulance isolates (p > 0.05). Conclusion. The frequency of MRSA isolates in hospital was significantly higher than in community, as well as the heterogeneous type of resistance. The frequency of BORSA isolates and production of betalactamases were higher among hospital Staphylococcus aureus isolates, but the difference is not significant.